The Relationship Between Fat Intake and Obesity with Hypertension in Men Aged 35-54 Years - Sembiring, Ariel Keriahen; Fenny Amaliya; Mara Imam Taufiq Siregar; Raihanah Suzan; Rita Halim (Journal of Medical Studies, 2025)
Background: Hypertension is a serious global health problem and a leading cause of morbidity and mortality worldwide. Dietary patterns, including high-fat intake and obesity, are modifiable risk factors strongly associated with hypertension. Objective: This study aims to analyze the relationship between fat intake and obesity with hypertension among men aged 35–54 years at Simpang IV Sipin Public Health Center. Methods: This study used an analytical observational design with a case-control approach. A total of 100 participants were included, consisting of 50 hypertensive cases and 50 controls. Fat intake was assessed using a 2×24-hour food recall and processed with NutriSurvey, while obesity was determined by BMI ≥ 25 kg/m². Data were analyzed using Chi-square and logistic regression. Results: A significant relationship was found between fat intake and hypertension (p < 0.001; AOR = 49.8, 95% CI: 8.35–297.11). There was no significant relationship between obesity and hypertension after multivariate analysis (p = 0.070; AOR = 4.47, 95% CI: 0.89–22.58). Conclusion: High fat intake is a dominant risk factor for hypertension in this population, while obesity showed no significant association after adjustment.